2009
DOI: 10.1111/j.1537-2995.2009.02377.x
|View full text |Cite
|
Sign up to set email alerts
|

High‐throughput red blood cell antigen genotyping using a nanofluidic real‐time polymerase chain reaction platform

Abstract: The nanofluidic genotyping platform described here provides an accurate method for predicting blood group phenotypes. The user-specified array layout provides flexibility of target selection and number of replicate determinations and is suitable for screening antigen types.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
42
0
5

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 34 publications
6
42
0
5
Order By: Relevance
“…Now that almost all the blood group genes have been cloned and the molecular bases of most antigens determined, it is feasible to conduct such a study with the use of high-throughput DNA-based methods. [122][123][124][125] Furthermore, the availability of rapid DNA sequencing methodologies presages an era in which mass screening of genes encoding red cell membrane proteins could be used to identify new polymorphisms of relevance to malarial invasion. Studies of this type, focused in tropical Africa, South East Asia, and Latin America, would provide a valuable database of new information about blood group diversity in populations inhabiting these regions not only for malarial epidemiologists but also for those investigating human susceptibility to new emerging infectious diseases given that zoonoses from wildlife in these regions have been identified as the most significant growing threat to global health of all emerging infectious diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Now that almost all the blood group genes have been cloned and the molecular bases of most antigens determined, it is feasible to conduct such a study with the use of high-throughput DNA-based methods. [122][123][124][125] Furthermore, the availability of rapid DNA sequencing methodologies presages an era in which mass screening of genes encoding red cell membrane proteins could be used to identify new polymorphisms of relevance to malarial invasion. Studies of this type, focused in tropical Africa, South East Asia, and Latin America, would provide a valuable database of new information about blood group diversity in populations inhabiting these regions not only for malarial epidemiologists but also for those investigating human susceptibility to new emerging infectious diseases given that zoonoses from wildlife in these regions have been identified as the most significant growing threat to global health of all emerging infectious diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Additional studies, including triplicate testing of 427 A-A donors, have shown more than 99% concordance with serology. 19 One advantage of the OpenArray platform is the user-specified target selection so that the platform can be adapted to screen specific ethnic groups.…”
Section: High-throughput Methodsmentioning
confidence: 99%
“…Compared to other commercially available genotyping techniques, HiFi-assay is clearly fitting the blood bank requirements in terms of safety, automation and throughput. Indeed, most of the numerous microarray-based genotyping techniques developed over the past few years (Di Cristofaro et al, 2007;Hashmi et al, 2007;Hopp et al, 2010;Karpasitou et al, 2008) are based on technologies often expensive, seldom easy to handle and difficult to integrate within highthroughput industrial blood supply processes. On the contrary, HiFi-technology main added-value remains its transfer to a fully automated, well-proven and secure high-throughput protocol.…”
Section: Application To Multiplex Blood Group Genotypingmentioning
confidence: 99%